Petroleum NAPL Depletion Estimates and Selection of Marker Constituents from Compositional Analysis. Issue 4 (29th October 2020) - DeVaull, George E.; Rhodes, Ileana A. L.; Hinojosa, Emiliano; Bruce, Cristin L.
Abstract: Spills and releases of hydrocarbons may result in zones of nonaqueous phase liquids (NAPL) within soils and groundwater. The NAPL will change, or "weather" over time due to a range of physical, chemical, and biological processes. Hydrocarbon constituents in environmental samples collected from NAPL‐impacted groundwater wells, sediments, or soils vary in composition over time due to weathering. The changing composition can be used to estimate mass depletion rates and trends for the bulk NAPL and for individual constituent chemicals relative to marker constituents which are less susceptible to weathering. Methods for the selection of marker constituents and for quantitatively and conservatively estimating NAPL depletion rates and trends over time are shown. Estimates are included for two sites with different NAPL mixtures present (crude oil and gasoline/diesel‐range product), for which depletion of half the initial total NAPL is estimated at 13.6 ± 2.9 years and 7.3 ± 1.8 years respectively, and with no active NAPL remediation at either site. Similar methods for oil or NAPL depletion estimates have often relied on a prior‐identified suite of presumed‐conserved marker constituents. The method presented here includes steps which identify the best set of analyzed candidate marker constituents in a NAPL mixture. This can confirm prior‐selected markers but is particularly useful for NAPL mixtures in which no prior‐identified marker constituents are present.